Civic And Moral Learning In America - Molnar, Christopher (Teaching History: A Journal of Methods, 2007)
Since the birth of the Republic, Americans have asked what sort of civic and moral education would best serve the needs of the nation. This edited collection gives a sense of the great variety "of ways in which that question has been answered throughout America’s history. Inspired by B. Edward McClellan’s Moral Education in America, the authors, most of them coming from the field of education, investigate the locations where civic and moral learning have taken place.